An Exploratory Study of Emotional Dysregulation Dimensions in Youth With Attention Deficit Hyperactivity Disorder and/or Bipolar Spectrum Disorders - Masi, Gabriele; Sesso, Gianluca; Pfanner, Chiara; Valente, Elena; Molesti, Agnese; Placini, Francesca; Boldrini, Silvia; Loriaux, Nina; Drago, Flavia; Montesanto, Anna Rita; Pisano, Simone; Milone, Annarita (Frontiers in Psychiatry, 2021)
Emotional Dysregulation (ED) is currently the most frequently used term to describe children with an impaired regulation of emotional states. Recent researches speculate whether ED may be a neurodevelopmental disorder itself, a shared risk factor or a common key feature of several psychiatric disorders, including, among the others, Attention Deficit Hyperactivity Disorder (ADHD) and Bipolar Spectrum Disorders (BSD). The association between ADHD and ED is one of the main reason of misconceptions in the definition of boundaries between ADHD and BSD, leading to the frequent misdiagnosis of ADHD as BSD. Since ED is a multidimensional concept, a novel instrument – the Reactivity, Intensity, Polarity and Stability (RIPoSt) scale – was recently developed to assess the different dimensions of ED, which could help in detecting specific ED profiles in clinical youths. Our study included 154 patients, aged 13.8 ± 2.3 years, diagnosed with either ADHD, BSD or comorbid condition and a school-based sample of 40 healthy control (HC) adolescents, aged 12.5 ± 1.2 years. The RIPoSt scale and the Child Behaviour Checklist were administered to both groups. Our results indicate that Affective Instability and Negative Emotionality subscales, as well as Negative Emotional Dysregulation, are higher in BSD, both pure and comorbid with ADHD, while Emotional Impulsivity is higher in the comorbid condition and similar in the ADHD and BSD alone group; all clinical groups scored higher than HC. Conversely, Positive Emotionality is similar among clinical groups and within them and HC. Our findings also support the validity of the RIPoSt questionnaire, since the instrument proved good-to-excellent internal consistency and strongly significant positive correlations were found with the CBCL – Dysregulation Profile, which is a sommonly used, indirect measure of ED. Hence, the five subscales of the RIPoSt can be reliably used as an effective tool to study the emotional dysregulation in different clinical conditions, to help disentangling the complex relationship between ADHD and juvenile BSD and to provide clinicians with crucial evidence for better diagnostic characterization and therapeutic indications